2019
DOI: 10.1038/s41598-019-40923-w
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA-seq study of wild type and Hox9,10,11 mutant developing uterus

Abstract: The uterus is a remarkable organ that must guard against infections while maintaining the ability to support growth of a fetus without rejection. The Hoxa10 and Hoxa11 genes have previously been shown to play essential roles in uterus development and function. In this report we show that the Hoxa9,10,11, Hoxc9,10,11, Hoxd9,10,11 genes play a redundant role in the formation of uterine glands. In addition, we use single cell RNA-seq to create a high resolution gene expression atlas of the developing wild type mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…An understanding of the source of cells that infiltrate the lung has remained elusive, however, as have the mechanisms of tumorigenesis, metastasis, invasion, and cystic remodeling Krymskaya and McCormack, 2017;McCormack et al, 2012). In the present study, scRNA-seq analysis of LAM lesions identified unique, non-pulmonary mesenchymal cells, which we termed LAM CORE cells, that share a high degree of transcriptomic similarity to the LAM CORE cells in uterus of an S-LAM patient and with myometrial and stromal cells (express high level of MME, FN1, COL3A1, HOXA10) from normal human and mouse uteri (Mucenski et al, 2019;Wu et al, 2018) . A prominent neural crest signature was also identified in pulmonary and uterine LAM CORE cells and in normal uterus.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…An understanding of the source of cells that infiltrate the lung has remained elusive, however, as have the mechanisms of tumorigenesis, metastasis, invasion, and cystic remodeling Krymskaya and McCormack, 2017;McCormack et al, 2012). In the present study, scRNA-seq analysis of LAM lesions identified unique, non-pulmonary mesenchymal cells, which we termed LAM CORE cells, that share a high degree of transcriptomic similarity to the LAM CORE cells in uterus of an S-LAM patient and with myometrial and stromal cells (express high level of MME, FN1, COL3A1, HOXA10) from normal human and mouse uteri (Mucenski et al, 2019;Wu et al, 2018) . A prominent neural crest signature was also identified in pulmonary and uterine LAM CORE cells and in normal uterus.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, uterine myocyte, epithelial, immune, endothelial and several stromal cell subtypes were identified (Figure 6a; Figure S15). Endometrial epithelia (expressing high level of KRT8, KRT18, EPCAM, CLDN3) and stromal cells (expressing high level of MME, FN1, COL3A1, HOXA10, VIM ) were defined based on the gene markers from the human and mouse uterus altas (Mucenski et al, 2019;Wu et al, 2018) . Hierarchical clustering of major cell types from LAM lung and LAM uterus demonstrated close correlation of LAM CORE cells from both tissues (Figure 6b).…”
Section: Identification Of Lam Core Cells In Uterus From a Patient Wimentioning
confidence: 99%
See 1 more Smart Citation
“…AP differentiation is driven by Hoxa9 in the oviduct, Hoxa10 in the uterus, Hoxa11 in the lower uterus and cervix, and Hoxa13 in the cervix and upper vagina (Du and Taylor 2015;Taylor et al 1997). Hoxc9-11 and Hoxd9-11 have some functional redundancy with Hoxa9-11 (Du and Taylor 2015;Mucenski et al 2019;Raines et al 2013). Disruption of Hoxa10 or combined disruption of Hoxa9-11 causes posteriorization of the reproductive tract with the anterior movement of stratified epithelium, including basal cells and extracellular matrix, from the cervix and upper vagina up into the uterus (Benson et al 1996;Mucenski et al 2019;Raines et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hoxc9-11 and Hoxd9-11 have some functional redundancy with Hoxa9-11 (Du and Taylor 2015;Mucenski et al 2019;Raines et al 2013). Disruption of Hoxa10 or combined disruption of Hoxa9-11 causes posteriorization of the reproductive tract with the anterior movement of stratified epithelium, including basal cells and extracellular matrix, from the cervix and upper vagina up into the uterus (Benson et al 1996;Mucenski et al 2019;Raines et al 2013). Neonatal GEN-exposed mice exhibited all of these characteristics and, in the uterus, expressed genes normally restricted to the cervix and upper vagina, including Trp63, Krt14, and Six1 (Suen et al 2016.…”
Section: Discussionmentioning
confidence: 99%